Especificação do micronúcleo FreeRTOS utilizando o método B - Galvão, Stephenson de Sousa Lima (2011)
This paper presents a contribution to the international Verified Software Repository effort through the formal specification of the microkernel FreeRTOS real-time system. Such specification was made in abstract level making use of the B method . For thus, properties of the microkernel were chosen and selected as specification requisites, which was constructed centered at the functionalities responsible for the utilization of these properties. This properties weres setting as specification requirements. The specification was constructed modeling the function of microkernel that implement this properties. This work intended to encourage the formal verification of FreeRTOS and also contribute to the formal creation of a microkernel real-time systems, based in FreeRTOS. Furthermore, this model brings a formal documentation point view of the microkernel, demonstrating features and how this internal states is changing. Finally, this work could be an example of specification of the actual system by the B method.